2001
DOI: 10.1099/00221287-147-4-1017
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular pH regulation by Mycobacterium smegmatis and Mycobacterium bovis BCG

Abstract: Mycobacteria are likely to encounter acidic pH in the environments they inhabit ; however intracellular pH homeostasis has not been investigated in these bacteria. In this study, Mycobacterium smegmatis and Mycobacterium bovis [Bacille Calmette-Gue! rin (BCG)] were used as examples of fast-and slowgrowing mycobacteria, respectively, to study biochemical and physiological responses to acidic pH. M. smegmatis and M. bovis BCG were able to grow at pH values of 45 and 50, respectively, suggesting the ability to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
158
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(165 citation statements)
references
References 38 publications
6
158
1
Order By: Relevance
“…3). To confirm this result, the ⌬⌿ was then measured with [ 3 H]tetraphenylphosphonium bromide (TPP ϩ ), as described (22)(23)(24). Results showed that ⌬⌿ in growing and nonreplicating hypoxic cells was identical ( Table 2), confirming that quiescent Mtb are able to maintain their membranes polarized to the same extent as growing cells.…”
Section: De Novo Atp Synthesis Is Essential For Survival Of Hypoxic Nmentioning
confidence: 78%
See 3 more Smart Citations
“…3). To confirm this result, the ⌬⌿ was then measured with [ 3 H]tetraphenylphosphonium bromide (TPP ϩ ), as described (22)(23)(24). Results showed that ⌬⌿ in growing and nonreplicating hypoxic cells was identical ( Table 2), confirming that quiescent Mtb are able to maintain their membranes polarized to the same extent as growing cells.…”
Section: De Novo Atp Synthesis Is Essential For Survival Of Hypoxic Nmentioning
confidence: 78%
“…The ⌬pH was measured by using [ 14 C]benzoic acid as a pH probe (23,24). We found a comparable ⌬pH in replicating and hypoxic nongrowing bacilli ( Table 2).…”
Section: De Novo Atp Synthesis Is Essential For Survival Of Hypoxic Nmentioning
confidence: 93%
See 2 more Smart Citations
“…The internal pH of cells was measured as described previously (36), with the following modifications. Samples of cultures were incubated with […”
Section: Determination Of Transcriptional Start Site (Tss)-mentioning
confidence: 99%